Effectiveness of psycho-educational intervention program on psychological status and blood glucose level of patients with type {u2161} diabetes mellitus in Gaza Strip - Emad Salem Kuhail; Nefissa Abdelkader; Warda Youssef (Cairo : Emad Salem Kuhail, 2012)
Depression and anxiety are common in patients with type 2 diabetes, adversely affecting quality of life, diabetes outcomes, and mortality. Depression, anxiety and uncontrolled blood glucose are disorder symptoms can be effectively treated with psycho-educational therapy based on cognitive behavior therapy (CBT), body, mind and spirit therapy
Thesis (Ph.D.) - Cairo University - Faculty of Nursing - Department of Nursing Science
Issued also as CD
Keywords: Psycho-educational intervention program; Psychological status; Type {u2161} diabetes mellitus